Expert System To Diagnose Beengal Cat Disease With Case Based Reasoning Method - Ananda Friska Utami; Jonson Manurung (Institute of Computer Science (IOCS), 2022)
At this time, many animal lovers keep pets. Cat or cattery owners sometimes find it difficult to diagnose pet cat diseases because cat diseases are not the same as human diseases, which are easy to diagnose and provide visible symptoms. Horas Cattery is a breeding ground and provider of pet cat adoption services, including Bengal cats. From the observations of the authors at Horas Cattery, understanding of the symptoms of cat diseases is still lacking, so they still rely on the expertise of experts manually, in addition, the cost for treatment to a veterinarian is very expensive and there are still few veterinarians. In this case, the research conducted at Horas Cattery uses the Case Based Reasoning method which is one of the methods of the expert system to diagnose Bengal cat disease because the method is based on knowledge from previous cases. Based on the research conducted, it was found that the case with the lowest weight was case 13, which was 0.2. Case 2 produces a high weight of 0.6667. So the results of calculations with weights show a confidence level of more than 60%.